A Stress Self‐Adaptive Silicon/Carbon “Ordered Structures” to Suppress the Electro‐Chemo‐Mechanical Failure: Piezo‐Electrochemistry and Piezo‐Ionic Dynamics - Zhao, Hongshun; Liang, Kang; Wang, Shijie; Ding, Zhengping; Huang, Xiaobing; Chen, Wenkai; Ren, Yurong; Li, Jianbin (Advanced science, 2023)
Construction of ordered structures that respond rapidly to environmental stimuli has fascinating possibilities for utilization in energy storage, wearable electronics, and biotechnology. Silicon/carbon (Si/C) anodes with extremely high energy densities have sparked widespread interest for lithium‐ion batteries (LIBs), while their implementation is constrained via mechanical structure deterioration, continued growth of the solid electrolyte interface (SEI), and cycling instability. In this study, a piezoelectric Bi0.5Na0.5TiO3 (BNT) layer is facilely deposited onto Si/C@CNTs anodes to drive piezoelectric fields upon large volume expansion of Si/C@CNTs electrode materials, resulting in the modulation of interfacial Li+ kinetics during cycling and providing an electrochemical reaction with a mechanically robust and chemically stable substrate. In‐depth investigations into theoretical computation, multi‐scale in/ex situ characterizations, and finite element analysis reveal that the improved structural stability, suppressed volume variations, and controlled ion transportation are responsible for the improvement mechanism of BNT decorating. These discoveries provide insight into the surface coupling technique between mechanical and electric fields to control the interfacial Li+ kinetics behavior and improve structural stability for alloy‐based anodes, which will also spark a great deal attention from researchers and technologists in multifunctional surface engineering for electrochemical systems. The decorated Bi0.5Na0.5TiO3 with intrinsic characteristic of stress response at the surface of active Si/C induces a local electric field, which significantly promotes Li+ diffusion at the cathode–electrolyte interphase. The application of the “initiative” function interphase material herein contributes to the comprehension of interphase engineering in a broad range of applications in the electrochemical and energy conversion community.